The effect of thermal comfort conditions during work hours on social disconnection - Christoforou, Rania; Pallubinsky, Hannah; Bardey, Janine; Rewitz, Kai; El-Mokadem, Mahmoud; Burgholz, Tobias; Müller, Dirk; Schweiker, Marcel (CLIMA 2022 conference, 2022)
Studies have focused on people’s physiological reactions to thermal conditions in indoor environments, neglecting the social consequences that could arise from them. Therefore, there is a gap in literature how these thermal comfort conditions could influence psychosocial aspects of our lives, such as how disconnected we feel from other people around us or how connected we feel with them, especially after being exposed to these conditions for many hours within an occupational context. This study attempted to address this gap in literature by exposing participants to two thermal conditions: a warm condition (28 ˚C) and a cool condition (21 ˚C) in a simulated office environment. The purpose of the study was to observe possible social consequences arising from a day at work under either of those conditions by focusing on social distance and empathy levels. 31 participants were recruited and exposed to both conditions, each condition at a different day (gap between days of at least one day for washout), and were asked to remain in the temperature-controlled environment for eight hours (between 9 a.m. and 5 p.m.). Additionally, they were asked to complete a series of questionnaires, investigating their levels of social disconnection and empathy before and after both testing days. The temperature of the room was monitored throughout the process. The difference observed between pre- and post-measures for both conditions was not significantly different with regards to the feelings of social disconnection, despite the difference in responses observed within the raw data for each condition. In contrast, the difference observed in empathy levels between pre- and post-measures was significantly different between conditions. Individuals exposed to the cool condition reported lower levels of empathy after exposure, while participants exposed to the warm condition exhibited higher empathy levels after exposure. The results suggest that thermal conditions could influence people’s levels of empathy, which could have consequences both within a work environment and in private life. Further research is needed to support this. Implications of these outcomes and recommendations for further research are discussed.